Thirty synchronous medullary and papillary thyroid carcinomas - Zhang, Daqi; Yang, Mingyu; Zhang, Xin; Wang, Cheng; Li, Kunlin; Wang, Hongbo; Chi, Hao; Sui, Chengqiu; Dionigi, Gianlorenzo; Sun, Hui (Frontiers in Endocrinology, 2023)
Background and Objectives. The synchronous occurrence of multiple neoplastic processes in the thyroid gland is unusual. We investigated the clinicopathological features of 30 medullary thyroid carcinomas (MTC) in association with papillary (PTC). Method. Retrospective analysis. Synchronous PTC/MTC in the same thyroid gland were classified into 4 subtypes: (type I) True mixed MTC/PTC, MTC and PTC closely intermingled. (Type II) Collision MTC/PTC, i.e. tumours that meet at the same site, invade each other and appear as a single mass in the thyroid gland, i.e. MTC and PTC merge. (Type III) Synchronous anatomically separate tumours in the same thyroid lobe, i.e. separated from each other by non-tumorous thyroid parenchyma. (Type IV) Synchronous tumours occurring in separate anatomical lobes or in the isthmus. Clinical and pathological data were reviewed. Location: Department of thyroid surgery, China-Japan Union Hospital, Jilin University. Time frame: 14 years (June 2008-November 2022). Results: Thirty patients were identified with an overall prevalence of 28621 (0.1%). 17 (56.7%) were male, 13 (43.3%) female, mean age 51.3±11.0 years, mean BMI 23.6±3.6kg/㎡. Mean duration of symptoms was 11.2±18.4 months. Mean calcitonin level was 133.7±196.4 pg/ml. Fine needle aspiration (FNA) was offered in 21 cases: 9 (42.9%) were suspected carcinoma, 9 (42.9%) PTC, 1 (4.8%) MTC, 2 (9.4%) MTC/PTC. Pathology revealed: type I 4 (13.3%), type II 2 (6.7%), type III 14 (46.7%), type IV 10 (33.3%). The mean diameter of MTC was 1.6±2.0cm, 18 (60%) were micro-MTC. The mean diameter of PTC was 0.9±1.9 cm, 26 (86.7%) were micro-PTC. In 16 (53.3%) micro-PTC/-MTC occurred in syncronous sequence. Four patients had a recurrence: 2 had to be re-operated due to MTC recurrence, 2 died due to distant metastases (bone, liver). Conclusion: We report an exceptional number of MTC/PTC in the same thyroid gland. This may be the most numerous case series reported in the literature. The clinical and pathological aspects as well as the results are presented.